Analisis Hasil Tes Potensi Skolastik sebagai Indikator Kesiapan Siswa Menghadapi Tes UTBK 2022 - Sriyati Sriyati (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The Scholastic Potential Test measures whether a student has the potential to enter college, in addition to academic ability. This study aims to analyze the scholastic potential test results of grade 12 students of SMAN 1 Situbondo as an indicator of student readiness to face the 2022 UTBK test. This study is descriptive, with the respondents being grade 12 students of SMA Negeri 1 Situbondo. The data collection method was carried out through a Try Out potential scholastic test consisting of 1) General Knowledge and Understanding, 2) General Reasoning, 3) Quantitative Knowledge, 4) Reading and Writing Comprehension, and 5) English language skills. The data were analyzed descriptively through the presentation of data in tables and graphs and analysis using independent sample t-test statistics. The results showed that the average score of 5 TPS components between science and social studies students was not significantly different (p > 0.05). Overall, the 5 TPS components score is still lower than half. General Knowledge and Comprehension scores and General Reasoning abilities are still higher than Quantitative Knowledge, Reading and Writing Comprehension, and English language skills. The conclusion is that the readiness of SMAN 1 Situbondo students to face the 2022 UTBK Test still needs to be improved.